Physical therapy and orthopaedic equipment-induced reduction in the biomechanical risk factors related to knee osteoarthritis: a systematic review and Bayesian network meta-analysis of randomised controlled trials. Issue 2 (9th February 2022) - Huang, Xi-Meng; Yuan, Fu-Zhen; Chen, You-Rong; Huang, Ying; Yang, Ze-Xi; Lin, Lin; Yu, Jia-Kuo
Abstract : Objective: Are physical therapy or orthopaedic equipment efficacious in reducing the biomechanical risk factors in people with tibiofemoral osteoarthritis (OA)? Is there a better therapeutic intervention than others to improve these outcomes? Design: Systematic review with network meta-analysis (NMA) of randomised trials. Data sources: PubMed, Web of Science, Cochrane Library, Embase and MEDLINE were searched through January 2021. Eligibility criteria for selecting studies: We included randomised controlled trials exploring the benefits of using physical therapy or orthopaedic equipment in reducing the biomechanical risk factors which included knee adduction moment (KAM) and knee adduction angular impulse (KAAI) in individuals with tibiofemoral OA. Data extraction and synthesis: Two authors extracted data independently and assessed risk of bias. We conducted an NMA to compare multiple interventions, including both direct and indirect evidences. Heterogeneity was assessed (sensitivity analysis) and quantified (I 2 statistic). Grading of Recommendations Assessment, Development and Evaluation assessed the certainty of the evidence. Results: Eighteen randomised controlled trials, including 944 participants, met the inclusion criteria, of which 14 trials could be included in the NMA. Based on the collective probability of being the overall best therapy for reducing the first peak KAM, lateral wedge insoles (LWI) plus knee brace was closely followed by gait retraining, and knee brace only. Although no significant difference was observed among the eight interventions, variable-stiffness shoes and neuromuscular exercise exhibited an increase in the first peak KAM compared with the control condition group. And based on the collective probability of being the overall best therapy for reducing KAAI, gait retraining was followed by LWI only, and lower limb exercise. Conclusion: The results of our study support the use of LWI plus knee brace for reducing the first peak KAM. Gait retraining did not rank highest but it influenced both KAM and KAAI and therefore it was the most recommended therapy for reducing the biomechanical risk factors.